MENGHADIRKAN TEKS-TEKS AUTENTIK DALAM KELAS BIPA DARING (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
Abstract Indonesian that taught as the foreign language in BIPA (Indonesian for Foreigners) classes and its authenticity are inseparable. Authenticity is related to the originality. In the context of BIPA learning, the authenticity can be presented in class activities related to contexts and real experiences, for examples students are asked to shop at the market, practice to bargain, practice to use public transportations, practice how to introduce themselves, interview native speakers, and many other authentic tasks. However, what makes it challenging today is that BIPA students cannot come directly to Indonesia and the learning process should be conducted online. Nonetheless, the authenticity can be still presented in authentic texts, not only in written but also in spoken. In addition, texts have complete thinking structures and understandings. Before presenting them in the class, teachers should understand the texts, situation context, culture context, authenticity, and types of text. The author also analyzes Graduate Competency Standards (SKL) of BIPA to identify types of text based on student’s level. Keywords: texts, situation contex, culture contex, authenticity, types of texts